2016
DOI: 10.1155/2016/3837623
|View full text |Cite
|
Sign up to set email alerts
|

Regular and Moderate Exercise Counteracts the Decline of Antioxidant Protection but Not Methylglyoxal‐Dependent Glycative Burden in the Ovary of Reproductively Aging Mice

Abstract: Population aging results in urgent needs of interventions aimed at ensuring healthy senescence. Exercise often results in healthy aging, yet many molecular mechanisms underlying such effects still need to be identified. We here investigated whether the age-dependent accumulation of oxidative and methylglyoxal- (MG-) related molecular damage could be delayed by moderate exercise in the mouse ovary, an organ that first exhibits impaired function with advancing age in mammals. CD1 female mice underwent two- or fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…As already reported 65 67 , the ratio of specific activities of coupled antioxidant enzymes is much better indicative of the efficiency of the antioxidative enzymatic defence than each activity alone. Statistically significant main effects of both MF exposure and time on the GPX/tSOD ratio were found (F = 186.1, P < 0.001 and F = 13.86, P < 0.01, respectively).…”
Section: Resultssupporting
confidence: 57%
“…As already reported 65 67 , the ratio of specific activities of coupled antioxidant enzymes is much better indicative of the efficiency of the antioxidative enzymatic defence than each activity alone. Statistically significant main effects of both MF exposure and time on the GPX/tSOD ratio were found (F = 186.1, P < 0.001 and F = 13.86, P < 0.01, respectively).…”
Section: Resultssupporting
confidence: 57%
“…One unit of activity was defined as 1 μ mol of S-D-lactoylglutathione produced min −1 . Conversely, Glo2 activity was assayed spectrophotometrically, at 25°C by recording the decrease in absorbance at 240 nm due to S-D-lactoylglutathione (0.3 mM) hydrolysis [21, 22]. One unit activity was defined as 1 μ mol S-D-lactoylglutathione hydrolyzed/min.…”
Section: Methodsmentioning
confidence: 99%
“…HG induced also an increase in GSSG/GSH ratio, which points to a pro-oxidant shift in the redox balance of glutathione. Upon redox stress, an important defense is provided by the enzymatic couple CAT/SOD, which ensures a rapid flux in the removal process of the redox couple O 2 − /H 2 O 2 [45,57,58]. Our assays revealed a prominent reduction in the CAT/SOD ratio upon HG, which is suggestive of an impairment of the O 2 − /H 2 O 2 detoxification process.…”
Section: Discussionmentioning
confidence: 77%
“…None of the three enzymes was modulated by HG at translational level ( p > 0.05, HG vs. CTR; Figure 5d–f). In addition, since the ratio of specific activities of coupled antioxidant enzymes much better reflects the status of the antioxidative enzymatic defense than each activity alone [57,58,59], we calculated the CAT/tSOD ratio, which is far more indicative of the overall ROS-targeting efficiency. Our data showed that HG strongly reduced the CAT over tSOD ratio, with respect to untreated cells ( p < 0.001, HG vs. CTR; Figure 5j).…”
Section: Resultsmentioning
confidence: 99%